Memoria de la herida y la revuelta fluyendo de los placeres "Madre de Dios" y Río Cruces. 2008/1598 - Illanes Oliva, María Angélica (Revista de Historia Social y de las Mentalidades, 2012)
The narration emerges from the experience and conscious of a territorial and geographic space: the goldwash stream named “Madre de Dios”, fluent of Cruces river, at Mariquina commune, South/Chile. The story is composed in two levels: one that emerges from the territorial experience as corporal memory of the narrator and other that surges from social history of Spaniard conquest and colony in south Chile, each level expressing itself in an specific language. In this way, the text is an exercise of thematic treatment as an “intra-historia” as an “inscritura”, rewriting historical events about resistance and historical social empowermentof nuestAmérica in South/Chile, through a present/past dialogue.